The Alternative Selection for Internet of Things (IoT) Implementation in Medical Rehabilitation - Rayi Adila Paramita, Muhammad Dachyar (International Journal of Advanced Science and Technology, 2020)
Medical rehabilitation services face problems in terms of limited duration and intensity of therapy. The implementation of the Internet of Things (IoT) in medical rehabilitation helps doctors and nurses to provide accurate care and faster recovery which could improve the service quality. This study aims to choose the best alternative IoT that can be implemented in medical rehabilitation units in hospitals by taking into account the factors of IoT implementation and hospital financial capability. The alternative options for implementation of IoT: Motion Gaming Rehabilitation, Virtual reality-based rehabilitation, Robot Therapy, Brain Computer Interfaces. The opinions of experts were used to identify and select factors and sub-factors that support the process of applying IoT in medical rehabilitation in hospitals. The Best Worst Method (BWM) method is used to obtain priority weighting from the criteria and sub-criteria for applying IoT. The Additive Ratio Assessment (ARAS) method is used to obtain the utility level of each alternative IoT. The Zero One Goal Programming method is used to decide whether the implementation of IoT is chosen based on limitations such as the ARAS utility level of each alternative, procurement and installation costs, training costs, and maintenance costs. The final result, virtual reality-based rehabilitation is chosen based on the factors of IoT implementation and the hospital financial capability.